THE ANALISIS SUPPLY CHAIN BERAS ORGANIK DI KABUPATEN SERDANG BEDAGAI - Abdul Rahman Cemda; Rahmat Suryanto Pirngadi; Liona Laksa (AGRIBIOS, 2025)
Serdang Bedagai is the largest organic rice producing district in Sumatra Utara. The largest producer of organic rice in North Sumatra Province, the increase in production of organic rice in Serdang Bedagai Regency is directly proportional to the increase in organic rice land area. Increased consumer demand for organic rice does not mean that farmers get greater profits, because there are several market players in the process of distributing organic rice to consumers. The purpose of this study is to determine the pattern of marketing marketing channels, marketing functions, profit margins received by each marketing actor as well as Farmer's Share. and Farmer's Share of the organic rice supply chain in Serdang Bedagai Regency. This research uses a descriptive qualitative analysis approach with a snowball sampling method. The results of this study found that there are four patterns of organic rice marketing channels in Serdang Bedagai Regency. The functions of organic rice marketing institutions in Serdang Bedagai Regency consist of the functions of buying, selling, drying, milling, weighing, packaging and transport. In channel 1 there is no marketing margin, because farmers directly sell organic rice to consumers with the Farmer's, share value of 100%. In marketing channel 2, the marketing margin of Rp. 7,000/Kg with a Farmer's Share value of 48.1%. In marketing channel 3, the marketing margin is Rp. 2,500/Kg with a Farmer's Share value of Share value of 40.6%, and in marketing channel 4 the marketing margin is Rp. 4,500/Kg with a Farmer's Share value of 36.1%.